Coal, Renewable, or Nuclear? A Real Options Approach to Energy Investments in the Philippines - Agaton, Casper (International Journal of Sustainable Energy and Environmental Research, 2017)
The Philippines is making a significant step to become energy independent by developing more sustainable sources of energy. The country sees investments in renewable energy and nuclear energy as promising alternatives to address the country’s problem in energy security. This paper evaluates the comparative attractiveness of either investing in alternative energy sources or continuing the use of coal for electricity generation in the Philippines. Applying the real options approach under coal price uncertainty, this study analyzes investment values and optimal timing of switching technologies from coal to renewable or nuclear energy. It also examines how negative externality and the risk of nuclear accident affect investment decisions. Results identify possible welfare losses from waiting or delaying investing in alternative energy. Negative externality favors investment in nuclear energy over coal, whereas the risk of nuclear accident favors investment in renewable energy.